Pengaruh Firm Size, Umur Perusahaan, Profitabilitas, Leverage, dan Growth Perusahaan terhadap Pengungkapan Corporate Social Responsibility - Febri Gunawan (JURNAL RISET AKUNTANSI TIRTAYASA, 2023)
This study aims to investigate the effect of firm size, company age, profitability, leverage, and firm growth on disclosure of corporate social responsibility in manufacturing companies in 2017-2019. The sample in this study is a manufacturing company selected using a purposive sampling method. Data analysis using multiple regression. The findings show that firm size and company age affect CSR disclosure in manufacturing companies. The influence of the other three variables is not significant.